1997
DOI: 10.1021/ja971226d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Acetylcholinesterase Dimer Complexed with Tacrine

Abstract: We have studied the dynamic properties of acetylcholinesterase dimer from Torpedo californica liganded with tacrine (AChE-THA) in solution using molecular dynamics. The simulation reveals fluctuations in the width of the primary channel to the active site that are large enough to admit substrates. Alternative entries to the active site through the side walls of the gorge have been detected in a number of structures. This suggests that transport of solvent molecules participating in catalysis can occur across t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
154
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 165 publications
(168 citation statements)
references
References 44 publications
11
154
2
1
Order By: Relevance
“…This difference could cause a difference in hydrogen bonding, electrostatic, and van der Waals interactions during the catalytic process, and result in a significant difference in free energies of activation. Nevertheless, the basic BChE mechanism for both enantiomers may resemble the common catalytic mechanism for ester hydrolysis in other serine hydrolases [32,39], including the thoroughly investigated AChE [40,41,42,43,44].…”
Section: Fundamental Reaction Pathway For Bche-catalyzed Hydrolysis Omentioning
confidence: 99%
“…This difference could cause a difference in hydrogen bonding, electrostatic, and van der Waals interactions during the catalytic process, and result in a significant difference in free energies of activation. Nevertheless, the basic BChE mechanism for both enantiomers may resemble the common catalytic mechanism for ester hydrolysis in other serine hydrolases [32,39], including the thoroughly investigated AChE [40,41,42,43,44].…”
Section: Fundamental Reaction Pathway For Bche-catalyzed Hydrolysis Omentioning
confidence: 99%
“…It has always been hard to simulate molecular dynamics on time scales that are biologically significant. Although it has been demonstrated that parallelism (using a spatial decomposition) can allow very large problems to be solved efficiently [12], the efficient use of parallelism to extend the time of simulation for a fixed-size problem has been elusive. Decomposition of the time domain provides one possible option [2,10].…”
Section: A Long-standing Challengementioning
confidence: 99%
“…the diisopropylphosphofluoridate hydrolase (DFPase) of the squid head ganglion (64), are homologous members of a small number of families displaying substantial structural similarity. In the case of the phosphotriesterase from Pseudomonas, which is known to hydrolyze both paraoxon and parathion (65), it has been clearly established that it shows no homology with human paraoxonase, which does not hydrolyze parathion (66). The molecular structure of the phosphotriesterase was recently solved to 2.1 Ä resolution (67,68).…”
Section: Work On Tcache Involves Two Principal Topicsmentioning
confidence: 99%
“…Molecular dynamics (MD) simulations have suggested that an alternative route of access to the active site might open via the concerted movement of residues W84, VI29, and G441 , while a more recent MD study has identified a number of "side entrances" to the gorge, all involving concerted movements of a number of side chains in the Q loop (C67-C92) of AChE (Wlodek et al, 1997b). As yet, no simple and predictive model for the clearance of the products of hydrolysis of ACh or BCh has been introduced into the treatment of the molecular traffic of substrates and ligands through the active site of ChEs.…”
Section: Introductionmentioning
confidence: 99%